Mental health literacy in Ghana: Implications for religiosity, education and stigmatization. (August 2021) - Adu, Peter; Jurcik, Tomas; Grigoryev, Dmitry
Research on Mental Health Literacy (MHL) has been growing internationally. However, the beliefs and knowledge of Ghanaians about specific mental disorders have yet to be explored. This vignette study was conducted to explore the relationships between religiosity, education, stigmatization and MHL among Ghanaians using a sample of laypeople (N = 409). The adapted questionnaire presented two vignettes (depression and schizophrenia) about a hypothetical person. The results revealed that more participants were able to recognize depression (47.4%) than schizophrenia (15.9%). Religiosity was not significantly associated with recognition of mental disorders but was positively associated with both social and personal stigma for depression, and negatively associated with personal and perceived stigma for schizophrenia. Moreover, education was found to be positively associated with disorder recognition, and negatively with perceived stigma. Finally, perceived stigma was positively associated with disorder recognition, whereas personal stigma for schizophrenia related negatively to recognition of mental disorders. In conclusion, education but not religiosity predicted identification accuracy, but both predictors were associated with various forms of stigma. Findings from this study have implications for MHL and anti-stigma campaigns in Ghana and other developing countries in the region.